Precise Optical Nyquist Pulse Synthesizer Digital-to-Analog Converter - Scheytt, J. Christoph; Schwabe, Tobias; Singh, Karanveer; Kress, Christian; Schneider, Thomas (Electronic-Photonic Integrated Systems for Ultrafast Signal Processing)
Abstract Optically assisted digital-to-analog converters (DACs) using Nyquist pulse sequences (NPSs) are presented and investigated. Therefore, NPSs are mathematically described and analyzed. Based on this, the operating principle of a precise optical Nyquist pulse synthesizer digital-to-analog converter (PONyDAC) is described. Possible architectures of PONyDAC are derived and compared in terms of performance and practicability. Moreover, the limits of PONyDAC systems and their superiority over classical electronic DACs are discussed. Furthermore, discrete building-block based implementations and monolithic implementations in electronic-photonic integrated circuits (EPICs) are presented. To enable a practicable monolithic integration, a shrinkage of the Mach-Zehnder modulators (MZMs) has been performed by applying forward-biased phase shifters (FB-PSs). These FB-PSs are analyzed and modeled to allow the precise and reliable design of PONyDAC systems with multiple MZMs. Finally, data conversion and data transmission experiments are carried out to demonstrate the systems functionality, quantify its performance, and prove their superiority over purely electronic DACs.

Electronic-Photonic Integrated Systems for Ultrafast Signal Processing

Forward-Biased Silicon Phase Shifter Modeling for Electronic-Photonic Co-Simulation and Validation in a 250 nm EPIC BiCMOS Technology - Schwabe, Tobias; Kress, Christian; Kruse, Stephan; Weizel, Maxim; Rhee, Hanjo; Scheytt, J. Christoph (Journal of Lightwave Technology)
Keywords: Integrated circuit modeling; Capacitance; Silicon; Modulation; Adaptation models; Semiconductor device modeling; Bandwidth; Data communication; electrooptical transmitter; equalization; free-carrier-plasma dispersion effect; modelling; optical modulator; phase shifter; silicon photonics

Analysis and Design of Forward Biased Silicon Photonics Phase Shifter Equalizer Circuits - Schwabe, Tobias; Kress, Christian; Sadiye, Babak; Kruse, Stephan; Scheytt, J. Christoph (IEEE Access)
Keywords: Optical attenuators; Equalizers; Phase shifters; Optical modulation; Electro-optic modulators; Optical amplifiers; Circuits; Silicon photonics; Optical saturation; Integrated circuit modeling; Data communication; equalization; electro-optical transmitter; silicon photonics; phase shifter; optical modulator; free-carrier plasma dispersion effect; driver architectures; biasing schemes

Electrooptical Integration of an Electronic Photonic Integrated Circuit Into Plastic Substrates Using Mid-Technology - Kruse, Stephan; Diri, Jabil; Mager, Thomas; Kress, Christian; Scheytt, J. Christoph (2025 55th European Microwave Conference (EuMC))
Keywords: Optical fibers; Integrated optics; Semiconductor device measurement; Laser radar; Optical device fabrication; Photonic integrated circuits; Microwave theory and techniques; Optical fiber devices; Plastics; Substrates; Microwave photonics; photonic radar; optical LO distribution; mechatronic integrated device (MID)

High-Speed Mach-Zehnder Modulator with Linear Segmented On-Chip Drivers in Photonic 45nm SOI-CMOS Technology - Kress, Christian; Schwabe, Tobias; Mihaylov, Martin Miroslavov; Scheytt, J. Christoph
We present an electronic-photonic co-designed Mach-Zehnder modulator with linear segment drivers in a photonic SOI-CMOS technology with an EO 3-dB bandwidth of ≥ 27 GHz and data transmission up to 64 Gbit/s without pre-emphasis.

Broadband Nyquist Pulse Generation on TFLN Platform for Integrated Quantum Source - Kress, Christian; Mihaylov, Martin Miroslavov; Schwabe, Tobias; Silberhorn, Christine; Scheytt, J. Christoph (PIERS Proceedings)
The generation of optically broadband Nyquist pulse sequences using an integrated Mach-Zehnder modulator (MZM) in a thin-film lithium-niobate (TFLN) platform with repetition rates of 5 to 32 GHz and optical bandwidths of up to 160 GHz is demonstrated. Nyquist pulse sequences with high optical bandwidth can be used as synchronization and control signals in quantum sources based on photon pair generation.

Compact, High-Speed Mach-Zehnder Modulator with On-Chip Linear Drivers in Photonic BiCMOS Technology - Kress, Christian; Schwabe, Tobias; Rhee, Hanjo; Scheytt, J. Christoph (IEEE Access)

Integrated Pulse Generator for Photon Pair Generation using Lithium Niobate on Insulator Technology - Kress, Christian; Schwabe, Tobias; Mihaylov, Martin Miroslavov; Silberhorn, Christine; Scheytt, J. Christoph

Simulation and Optimization of Low-Loss Photonic Coupling Structures for TFLN Integrated Circuits for Quantum Applications - Mihaylov, Martin Miroslavov; Kress, Christian; Scheytt, J. Christoph

Generation of 100 GHz Periodic Nyquist Pulses using Cascaded Mach-Zehnder Modulators in a Silicon Electronic-Photonic Platform - Kress, Christian; Schwabe, Tobias; Silberhorn, Christine; Scheytt, J. Christoph (Conference on Lasers and Electro-Optics (CLEO) 2023)
A frequency-flexible Nyquist pulse synthesizer is presented with optical pulse bandwidths up to fopt=100 GHz and repetition rates equal to fopt/9, fabricated in an electronic-photonic co-integrated platform utilizing linear on-chip drivers.

Analysis of Phase Noise in Waveguide-integrated Optical Test Structures in Silicon Photonics - Surendranath Shroff, Vijayalakshmi; Kress, Christian; Bahmanian, Meysam; Scheytt, J. Christoph (2023 PhotonIcs & Electromagnetics Research Symposium (PIERS),)
This paper experimentally investigates and interprets the e®ects of noise and non- linearity in a silicon photonic optical test structure. For the analysis di®erent optoelectronic phase noise measurement techniques are used. Our tests focuses on the performance of integrated opti- cal test structures using femtosecond pulses in the 1550nm spectral range. A primary objective is to understand the behaviour of silicon photonic waveguides that can be further employed in the implementation of an optoelectronic phase-locked loop (OEPLL) in silicon photonics technology. A comparison of our results, as well as a discussion on the di®erent optoelectronic phase noise measurement techniques are presented. Our ¯ndings provide insights that can be leveraged to optimize the design and performance of ultra-low phase noise on-chip OEPLL systems locking to mode-locked laser (MLL) signals. In the future such systems can be essential for advanced communication and sensing applications.

Broadband Mach-Zehnder Modulator with Linear Driver in Electronic-Photonic Co-Integrated Platform - Kress, Christian; Schwabe, Tobias; Rhee, Hanjo; Kerman, Sarp; Scheytt, J. Christoph (Optica Advanced Photonics Congress 2022)
A monolithically integrated electronic-photonic Mach-Zehnder modulator is presented, incorporating electronic linear drivers along photonic components. An electro-optical 3 dB & 6 dB bandwidth of 24 GHz and 34 GHz respectively was measured. The on-chip drivers decrease the V π by a factor of 10.

Locking of microwave oscillators on the interharmonics of mode-locked laser signals - Bahmanian, Meysam; Kress, Christian; Scheytt, J. Christoph (Optics Express)
In this paper, the theory of phase-locking of a microwave oscillator on the interharmonics, i.e. non-integer harmonics, of the repetition rate of the optical pulse train of a mode-locked laser (MLL) is developed. A balanced optical microwave phase detector (BOMPD) is implemented using a balanced Mach-Zehnder modulator and is employed to discriminate the phase difference between the envelope of the optical pulses and the microwave oscillator. It is shown mathematically that the inherent nonlinear properties of BOMPD with respect to the microwave excitation amplitude can be used for interharmonic locking. The characteristic functions of the phase detector for interharmonic locking are derived analytically and are compared with the measurement results. An opto-electronic phase-locked loop (OEPLL) is demonstrated whose output frequency locks on interharmonics of the MLL repetition rate when an appropriate modulator bias and sufficient RF amplitude are applied. Thus, for the first time theory and experiment of reliable locking on interharmonics of the repetition rate of a MLL are presented.

Analysis of the effect of jitter and non-idealities on photonic digital-to-analog converters based on Nyquist pulses - Singh, Karanveer; Kress, Christian; Mandalawi, Younus; Misra, Arijit; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Next-Generation Optical Communication: Components, Sub-Systems, and Systems XI)

Emulation of integrated high-bandwidth photonic AWG using low-speed electronics - Singh, Karanveer; Meier, Janosch; Kress, Christian; Misra, Arijit; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Next-Generation Optical Communication: Components, Sub-Systems, and Systems XI)

Reconfigurable and real-time high-bandwidth Nyquist signal detection with low-bandwidth in silicon photonics - Misra, Arijit; Kress, Christian; Singh, Karanveer; Meier, Janosch; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Optics Express)
We demonstrate for the first time, to the best of our knowledge, reconfigurable and real-time orthogonal time-domain detection of a high-bandwidth Nyquist signal with a low-bandwidth silicon photonics Mach-Zehnder modulator based receiver. As the Nyquist signal has a rectangular bandwidth, it can be multiplexed in the wavelength domain without any guardband as a part of a Nyquist-WDM superchannel. These superchannels can be additionally multiplexed in space and polarization. Thus, the presented demonstration can open a new possibility for the detection of multidimensional parallel data signals with silicon photonics. No external pulse source is needed for the receiver, and frequency-time coherence is used to sample the incoming Nyquist signal with orthogonal sinc-shaped Nyquist pulse sequences. All parameters are completely tunable in the electrical domain. The feasibility of the scheme is demonstrated through a proof-of-concept experiment over the entire C-band (1530 nm–1560 nm), employing a 24 Gbaud Nyquist QPSK signal due to experimental constraints on the transmitter side electronics. However, the silicon Mach-Zehnder modulator with a 3-dB bandwidth of only 16 GHz can process Nyquist signals of 90 GHz optical bandwidth, suggesting a possibility to detect symbol rates up to 90 GBd in an integrated Nyquist receiver.

Flexible Time-Domain De-Multiplexing of Nyquist OTDM Channels by Orthogonal Sampling in Silicon Photonics - Misra, Arijit; Singh, Karanveer; Meier, Janosch; Kress, Christian; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Conference on Lasers and Electro-Optics)
We report for the first time, inter-symbol-interference (ISI) free demultiplexing of Nyquist optical time division multiplexed (OTDM) signals using a reconfigurable orthogonal sinc-pulse sampling enabled by silicon photonic Mach-Zehnder Modulators.

High Modulation Efficiency Segmented Mach-Zehnder Modulator Monolithically Integrated with Linear Driver in 0.25 \textmum BiCMOS Technology - Kress, Christian; Singh, Karanveer; Schwabe, Tobias; Preußler, Stefan; Schneider, Thomas; Scheytt, J. Christoph (OSA Advanced Photonics Congress 2021)
We present a monolithically integrated electronic-photonic Mach-Zehnder modulator with a linear, segmented driver on the same silicon substrate. As metric for the modulation efficiency, the external V$π$ is hereby reduced to only 420 mV.
Keywords: Analog to digital converters; Extinction ratios; Grating couplers; Modulation; Modulators; Phase shift

Analysis of the effects of jitter, relative intensity noise, and nonlinearity on a photonic digital-to-analog converter based on optical Nyquist pulse synthesis - Kress, Christian; Bahmanian, Meysam; Schwabe, Tobias; Scheytt, J. Christoph (Opt. Express)
An analysis of an optical Nyquist pulse synthesizer using Mach-Zehnder modulators is presented. The analysis allows to predict the upper limit of the effective number of bits of this type of photonic digital-to-analog converter. The analytical solution has been verified by means of electro-optic simulations. With this analysis the limiting factor for certain scenarios: relative intensity noise, distortions by driving the Mach-Zehnder modulator, or the signal generator phase noise can quickly be identified.
Keywords: Analog to digital converters; Diode lasers; Laser sources; Phase noise; Signal processing; Wavelength division multiplexers